Transactions on Computational Science XXVII - Gavrilova, Marina L.; Tan, C.J. Kenneth (Transactions on Computational Science,, 2016)
The LNCS journal Transactions on Computational Science reflects recent developments in the field of Computational Science, conceiving the field not as a mere ancillary science but rather as an innovative approach supporting many other scientific disciplines. The journal focuses on original high-quality research in the realm of computational science in parallel and distributed environments, encompassing the facilitating theoretical foundations and the applications of large-scale computations and massive data processing. It addresses researchers and practitioners in areas ranging from aerospace to biochemistry, from electronics to geosciences, from mathematics to software architecture, presenting verifiable computational methods, findings, and solutions, and enabling industrial users to apply techniques of leading-edge, large-scale, high performance computational methods. This, the 27th issue of the Transactions on Computational Science journal, is devoted to the topic of high-performance computing. It contains eight full papers, covering the areas of cloud middleware, multi-processor systems, quantum computing, optimization, and secure biometric-based encryption methods.